Actitudes hacia la ciencia a lo largo de BUP y COU: un estudio longitudinal - Espinosa García, J.; Román Galán, T. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1995)
We have performed a longitudinal study among BUP and COU students, from fourteen to eighteen years old, and their attitudes to Science. This attitude becomes neither linear nor more negative through successive years. On the contrary, we have observed a «saw tooth» profile.